FTIR- and UHPLC-Q-Orbitrap HRMS-based metabolomics of sonchus arvensis extracts and evaluation of their free radical scavenging activity - Mohamad Rafi; Triyani Hasanah; Alfi Hudatul Karomah; Ade Heri Mulyati; Trivadila; Min Rahminiwati; Achmadi, Suminar Setiati; Dyah Iswantini (Penerbit Universiti Kebangsaan Malaysia, 2022)
Sonchus arvensis, known as sowthistle, belongs to Asteraceae and contains numerous phenolic acids and flavonoids that exhibit antioxidants. The type of extraction solvent will affect biological activity level, resulting in different metabolite profiles that metabolomics approaches can evaluate by fingerprint analysis using FTIR spectrophotometry and UHPLC-Q-Orbitrap HRMS. Furthermore, the FTIR spectra and the metabolite profile of UHPLC-Q-Orbitrap HRMS were grouped using principal component analysis (PCA). This study aimed to clustering S. arvensis extracts based on different extracting solvents using the FTIR spectra and the detected metabolites and evaluate the free radical scavenging activity. The 50% ethanol extract gave higher free radical scavenging activity and more metabolites than the ethanol p.a. and water extracts. It indicates that the free radical scavenging activity is affected by the metabolites contained in the extract. Using a combination of the FTIR spectra and the peak area of the identified metabolites, S. arvensis extract can be grouped according to the extracting solvent. Thus, the extracting solvent affects the composition of the metabolites, resulting in different free radical scavenging activity levels.